Landscape Pattern, Stream Network Structure, and Fish Distribution in Headwater Catchments - Torgersen, Christian (University of Washington Water Center, 2006)
Torgersen will describe a study investigating coastal cutthroat trout. He will evaluate landscape disturbance, spatial patterns, and explanatory models. Finally, he will offer conclusions about the links between geology, geomorphology, and fish distribution. He will also discuss the relationships between fish distribution, hydrology, and cumulative watershed effects. He will review the use of digital elevation models and remote sensing to predict fish distribution at broad scales.
Keywords: Oncorhynchus; geographical distribution; landscape ecology; simulation models; geology; hydrogeology; geomorphology; watersheds; watershed hydrology; digital elevation models; remote sensing; models; water